Molecular screening programmes for precision medicine: lessons learned from personalized medicine trials. Issue 5 (2nd September 2016) - Aguilar, Helena; Sanchez, Elena; Braña, Irene; Vivancos, Ana; Rodon, Jordi
ABSTRACT: Introduction : The efficacy of targeted therapies in patient populations selected on the basis of the molecular features of their tumours has gained tremendous attention and is shifting the current focus of treatment to biomarker-driven clinical trials. Molecularly-selected patients are the best-case-scenario for proof-of-concept in the early development of new drugs and a potential path for registration. Developing targeted therapies in biomarker-selected patient populations can also face additional challenges. Areas covered : Different approaches in order to select patients for specific treatments are possible, using modern and relatively inexpensive genotyping platforms, but quite often logistics are their bottleneck. Main stakeholders may have different points of view on the co-development of drug-test (Pharma, diagnostic companies, clinical investigators, patients, Regulatory Agencies), which will influence how clinical research is implemented, and ultimately its feasibility. Expert commentary : Molecular prescreening programs vary in their focus of attention, with two clearly differentiated tactics: finding patients for trials or finding trials for patients. Sample management, type of assays and platforms used, logistics, turn-around time, and cost will all depend on the scope of the prescreening program and will define its returns. In conclusion, to optimize benefit for individual patients a biomarker-driven setting for clinical trials is a rational approach.